Are Rural Students Receiving FAPE? A Descriptive Review of IEPs for Students With Social, Emotional, or Behavioral Needs. Issue 1 (January 2021) - Hott, Brittany L.; Jones, Beth Ashby; Rodriguez, Jacqueline; Brigham, Frederick J.; Martin, Amelia; Mirafuentes, Minerva
Students who are eligible to receive special education and related services are entitled to a free and appropriate public education (FAPE) including the necessary emotional, behavioral, and social supports to access the general curriculum. This study explores Individualized Education Program (IEP) plans of students with disabilities who have social, emotional, or behavioral needs served in five rural independent school districts. Specifically, the study sought to investigate (a) whether the present level of academic and functional performance (PLAAFP) and annual goals demonstrated congruence and (b) whether the degree to which the IEP documents conform to both procedural and substantive requirements for development. A review of 126 IEPs suggests that although IEPs are somewhat compliant, they fail to comprehensively address student needs or align across areas, violating the spirit of Individuals with Disabilities Education Improvement Act. Recommendations and future areas of inquiry are provided.